Factors Related with Lower Limbs Varicose Veins on Sales Promotion Girl and Salesperson - Nurul Misbahiyah; Siti Musyarofah; Cahyo Suraji (LPPM STIKES KENDAL, 2020)
Lower Limbs Varicose Veins causes aesthetics problems in terms of appearance problems, still patient has many health complains such as pain, burning feelings in their limbs, edema, even until ulcers. Many this complains may affect their social and economic life consequence of their productivity decline, seclude, and their medical care requirement. This research is aimed at preventing triggers factors and reducing all predisposing factors which can lead to increased all patient productivity. This study apply a quantitative research with observational analytic survey method cross sectional study and using total sampling method on 62 respondents from Sales Promotion Girl and Salesperson done in May 2017. Non-parametric test rank spearman used for data processing. This study result an opposite relationship on pregnancy variable (sig. 0.0001 with correlation coefficient value -0.497), which means respondents who was in pregnant doesn’t has any lower limbs varicose veins symptoms, this may influenced by many non-pregnant respondents who has lower limbs varicose veins symptoms too. Moderate relationship value on long standing variable (sig. 0.0001 with correlation coefficient value 0.456) and wearing heels variable (sig. 0.0001 with correlation coefficient value 0.497), meanwhile obesity variable (sig. 0.044 with correlation coefficient value 0.257) and labour period variable (sig. 0.008 with correlation coefficient value 0.335) gets a low relationship value. Variables indicated a relationship with Lower Limbs Varicose Veins, then Sales Promotion Girl and Salesperson expected to do routine exercise and stretching muscles after working.